Charakter prawny umów kompensacyjnych - Olejniczak, Adam (Wydział Prawa i Administracji UAM, 1991)
The article presents the analysis of legal qualification of counterpurchase contracts in the light of the Polish law. The subject-matter of the analysis are: the counterpurchase contract as a final sale contract, as a contract for negotiations, as a preliminary contract, and as a frame contract. The author is of the opinion that counterpurchase contracts may most often be qualified as frame contracts.
Legal character of counterpurchase contracts